'ALSPAC' infant morbidity and Council Tax Band: doctor consultations are higher in lower bands. - Beale N; Peart C; Kay H; Taylor G; Boyd A; Herrick D (European Journal of Public Health, 2010)
Background: The discrepancy between the occurrence of disease and the risk of consulting a doctor is well known, but whether or not it is socially governed is uncertain and could have important implications for primary care manpower and resource allocation. The aim of the study was to investigate whether (i) reported occurrence of common symptoms in infancy and (ii) consulting rates for those symptoms, are associated with socio-economic status as marked by Council Tax Valuation Band (CTVB). Methods: Compound cross-sectional analysis of data was obtained from sequential parental questionnaires. Data were taken from Avon Longitudinal Study of Parents and Children of over 14 000 responders from Avon county since 1991. Comparative analyses by CTVB and other covariables were carried out. Results: Final study group of nearly 10 000: diarrhoea, wheeze and accidental injuries moderately associated with CTVB but consulting behaviour for all morbidity bar earache strongly associated with CTVB, the lower the band the higher the clinical burden. Conclusion: The children from more modest homes are more likely to be taken to a doctor for everyday symptoms: for infant morbidity, the lower the CTVB of home address, the higher the clinical burden for UK general practices.